Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15

Immobilized invertase - Kotwal, S. M.; Shankar, V. (Biotechnology Advances, 2009)
Invertase is a commercially important enzyme used for the hydrolysis of sucrose. The hydrolysis of sucrose yields an equimolar mixture of glucose and fructose, known as invert syrup, is widely used in food and beverage industries. This enzyme is also used for the manufacture of artificial honey, plasticizing agents used in cosmetics, pharmaceutical and paper industries as well as enzyme electrodes for the detection of sucrose. Immobilization of invertase and its biotechnological applications are reviewed. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Applications; Immobilization; Invert syrup; Saccharase